Antioxidant and Anticancer Activities of Silver Nanoparticles Synthesized Using Cinnamon Extracts - Khalidah Khalaf Jabbar; Mohamed Bouaziz (Al-Mustansiriyah Journal of Science, 2025)
Background: There is great interest in developing plant-based nanoparticles due to their unique chemical and physical properties, which make them an excellent alternative to chemical drugs that fight bacteria and protect cells from damage. Objective: Green synthesis of silver nanoparticles using cinnamon, characterization and evaluation of them as antioxidants, and investigation of their effect on the HepG-2 cell line. Methods: The study involved the green synthesis of Ag NPs/cinnamon, its characterization using XRD, TEM, and GC-MS techniques, and the evaluation of its activity as DPPH antioxidants as well as activity against the HepG-2 cell line. Results: During analysis, it was found that the diameter of the nanoparticles ranged from approximately 19 to 100 nm. The results indicated that the crystal sizes ranged from 12.68 to 29.76 nm, with an average crystal size of 22.335 nm. Cinnamon contains 25 chemical compounds with high antioxidant activity, such as 3-phenyl-(cinnamaldehyde), coumarin, cis-calamine, trans-calamine, oleic acid, (Z)-9-octadecenoic acid, and octadecenoic-9-enoic acid. The nanoparticles inhibited 62% of free radicals, confirming that Ag NPs/cinnamon has good free radical scavenging activity at low concentrations and can function as antioxidants. The results showed that Ag NPs/cinnamon induced greater damage to HepG-2 hepatocytes than to HFF hepatocytes. At a concentration of 1 mg/ml, silver nanoparticles inhibited cytotoxicity and increased cell viability. Compared with the control group (HFF), the IC50 value was 48.41 mg/ml, and the toxicity was 105.1 mg/ml, respectively. Conclusions: Silver nanoparticles combined with cinnamon exhibited significant antioxidant properties, indicating their potential as promising free radical scavengers. Additionally, the synthesized Ag NPs/cinnamon exhibited notable activity against the HepG-2 cell line.